2009
DOI: 10.1359/jbmr.080505
|View full text |Cite
|
Sign up to set email alerts
|

Bone Disease in Thalassemia: A Frequent and Still Unresolved Problem

Abstract: Adults with β thalassemia major frequently have low BMD, fractures, and bone pain. The purpose of this study was to determine the prevalence of low BMD, fractures, and bone pain in all thalassemia syndromes in childhood, adolescence, and adulthood, associations of BMD with fractures and bone pain, and etiology of bone disease in thalassemia. Patients of all thalassemia syndromes in the Thalassemia Clinical Research Network, ≥6 yr of age, with no preexisting medical condition affecting bone mass or requiring st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
219
2
6

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 217 publications
(247 citation statements)
references
References 41 publications
(55 reference statements)
20
219
2
6
Order By: Relevance
“…Osteoclasts were homogenized in chloroform/methanol/TRISHCl 50 mM pH 7.4 (2: 5 -2-AG as internal deuterated standards. The extract was purified and the eluted fraction containing AEA and 2-AG was analyzed as previously described.…”
Section: Endocannabinoid Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Osteoclasts were homogenized in chloroform/methanol/TRISHCl 50 mM pH 7.4 (2: 5 -2-AG as internal deuterated standards. The extract was purified and the eluted fraction containing AEA and 2-AG was analyzed as previously described.…”
Section: Endocannabinoid Measurementsmentioning
confidence: 99%
“…[1][2][3][4] The pathogenesis of OP is multifactorial and includes environmental (diet and lifestyle), iatrogenic (drugs), acquired (bone marrow expansion, hemochromatosis, hepatitis, deficiency of growth hormone or insulin growth factor I, and hypogonadism) and genetic factors. [1][2][3][4][5][6][7] The relative contribution of these factors to TM-OP is uncertain, and the role of iron overload and iron chelation therapy is the subject of increasing interest. Interestingly, reports have shown different responses to bisphosphonate treatment between patients with TM and those with thalassemia intermedia: in a prospective study, individuals with TM were shown to have high turnover bone disease and responded more favorably to treatment with pamidronate and hormone replacement therapy, as compared with patients with thalassemia intermedia.…”
Section: Introductionmentioning
confidence: 99%
“…11,20,31,33 Vogiatzi and associates found that adolescence is a critical period for the augmentation of loss of bone mass in thalassemia and suggested that bone turnover plays an important role in this process. 33 These findings may better explain why our patients, who were all < 16 years of age, showed no significant changes in BMD. In our previous study of transplant patients we found that patients with a mean age of 7.4 years did not have z scores < -2 initially and 12 months after HSCT.…”
Section: Discussionmentioning
confidence: 99%
“…In some studies (23,24), in order to reduce the u n c o r r e c t e d p r o o f influence of bone size on BMD measurements in the growing skeleton, the apparent volumetric density of the lumbar spine has been calculated using a specific formula (25). In TM patients, it is very common to find low BMD values (osteopenia or osteoporosis) and in some studies up to 90%, even in optimally transfused and chelated patients, as is shown in Table 1 (7,(26)(27)(28)(29)(30)(31). Prevalence of fractures in TM patients is depicted in Table 2 and ranges from 16% to 49%, depending on study population and method of data collection (3,5, [32][33][34][35].…”
Section: Bone Metabolism In Tm Patientsmentioning
confidence: 99%
“…Prevalence of fractures in TM patients is depicted in Table 2 and ranges from 16% to 49%, depending on study population and method of data collection (3,5, [32][33][34][35]. Extremity fractures are the most common (27), in particular at the upper extremity (5). Vertebral fractures are usually underestimated, and their prevalence varies from 2.6% to 13% (27,36).…”
Section: Bone Metabolism In Tm Patientsmentioning
confidence: 99%